The Lexical Semantics of Safara in the Qur’anic Discourse: A Contextual and Linguistic Analysis - Syifa Pauzia Habsi; Neli Asmaniah; Singgar Mantahari Dalimunthe (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Semantic studies of Qur’anic vocabulary are often confined to partial lexical interpretations that separate the physical and metaphysical dimensions of meaning. This study highlights the semantic complexity of the lexeme safara (سفر), which possesses various semantic derivations—ranging from travel (safar), illumination (asfara), to angels (safarah)—that are frequently misunderstood as unrelated homonyms. The aim of this research is to reconstruct the semantic structure of the word safara in order to identify the core meaning that binds these variants within the Qur’anic worldview. Using a descriptive qualitative method with the Semantic Field Theory approach and componential meaning analysis, this study examines eleven Qur’anic verses containing derivations of the root safara. The findings reveal a novel insight: the derivations of safara do not merely denote “travel,” but rather revolve around the philosophical concept of al-inkisyāf (disclosure or unveiling). Safar signifies the unveiling of one’s true character and the discovery of new places; asfara denotes the unveiling of light from the darkness of dawn; and safarah refers to the unveiling of written revelation conveyed by angels. The theoretical implication of this study demonstrates that the Qur’anic derivational system integrates natural phenomena, human activities, and metaphysical entities within a coherent semantic network, while also challenging conventional lexical interpretations that limit safara solely to the notion of physical mobility.